A la luz del sueño (2020)
A la luz del sueño is a design solution for children with sleep disorders using the spectrum light and colors. This project starts with the observation of a baby who manifests problems to sleep in specific times of the day and nocturnal awakenings. For this reason, this works integrates three elements, color, children and circadian rhythm of sleep, to find an ambiental tool to promote and regulate the biological sleeps habits. A la luz del sueño, presents different experiments processes based on light color to find witch characteristics promote the induction of sleep, its prolongation and defined sleep...